1998
DOI: 10.1021/ie980021q
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Vapor−Liquid Equilibria for Alkane Mixtures

Abstract: A newly proposed united-atom force field is used to predict the phase behavior of binary mixtures of long and short alkanes over wide ranges of temperature and pressure. Given the chemical similarity of the components, no adjustable binary parameters are introduced. In general, agreement with experiment is satisfactory. Two commonly used equations of state are also used to describe experimental coexistence curves. In the absence of binary data, it is found that molecular simulations provide a fairly reliable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 23 publications
5
61
0
Order By: Relevance
“…Molecular dynamics simulations of the same systems were then conducted using the NERD UA force field, which has been shown to reproduce the thermodynamic properties ͑including phase behavior͒ of alkanes with good accuracy. 1,18 Our results suggest that united-atom force fields are capable of describing simultaneously the equilibrium thermodynamic properties and several dynamic aspects of intermediate to long alkanes.…”
Section: Introductionmentioning
confidence: 80%
“…Molecular dynamics simulations of the same systems were then conducted using the NERD UA force field, which has been shown to reproduce the thermodynamic properties ͑including phase behavior͒ of alkanes with good accuracy. 1,18 Our results suggest that united-atom force fields are capable of describing simultaneously the equilibrium thermodynamic properties and several dynamic aspects of intermediate to long alkanes.…”
Section: Introductionmentioning
confidence: 80%
“…In previous publications we have showed that this is possible for binary mixtures of short and long normal alkanes and branched alkanes. 8,9 Unfortunately, to the best of our knowledge, experimental data for mixtures with alkenes are limited; direct comparison of simulation results to experiments for mixtures was, therefore, minimal in this article.…”
Section: Resultsmentioning
confidence: 99%
“…Industrial applications have often relied on empirical correlations and semitheoretical equations of state to predict phase equilibria; unfortunately the predictive capabilities of commonly used equations of state of mixtures have recently been called into question. 9,10 Given the chemical simplicity of alkanes and olefins, molecular simulations could provide a useful complement or alternative in the study and description of the phase behavior of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…For nonbonded, unlike pair interactions, Lorentz-Berthelot combining rules are used, which in previous work have been shown to be suitable for alkane mixtures. 15 In all calculations, a cutoff radius of 10.0 Å is employed for Lennard-Jones interactions, and standard tail corrections 9,16 are implemented. The NERD force field has been shown to provide good agreement with experimental phase-equilibria data for pure alkanes and alkenes, and their binary and ternary mixtures.…”
Section: Molecular Modelsmentioning
confidence: 99%